Matrix Production in Chondrocytes Transfected with Sex Determining Region Y-Box 9 and Telomerase Reverse Transcriptase Genes: An In Vitro Evaluation from Monolayer Culture to Three-Dimensional Culture - Ismail Zainol (Tanjong Malim, 2019)
Matrix Production in Chondrocytes Transfected with Sex Determining Region Y-Box 9 and Telomerase Reverse Transcriptase Genes: An In Vitro Evaluation from Monolayer Culture to Three-Dimensional Culture by Ismail Zainol